Design and Simulation of Two-stage HMCVT based on Sanitation Vehicle - Huang Guoqing; Chen Cong; Yu Yapeng (Jixie chuandong)
In view of the current sanitation vehicle will cause a lot of power loss in operation,according to the actual situations and needs of sanitation vehicles,a two-stage hydro-mechanical continuously variable transmission（ HMCVT） is proposed,and the analysis of speed regulation characteristic and power characteristic is carried out. The results show that it can combine the advantages of input-split transmission and output-split transmission. By using the AMESim software,the physical model of complex HMCVT is built. The simulation analysis of speed regulation characteristic,load characteristic,start characteristic in transmission system and speed regulation characteristics in driving are completed. The simulation results show that the transmission can withstand the impact of shock loads,when changing speed in the start and driving,the displacement ratio adjustment handle should be adjusted slowly to make the stable adjustment come true. It is important to improve the work efficiency of sanitation vehicle.